Economic Voting under Coalition Governments: Evidence from Germany*. Issue 1 (8th October 2013) - Debus, Marc; Stegmaier, Mary; Tosun, Jale
<x content-type="archive" xml:space="preserve">Abstract</x> This article analyzes the impact of economic voting in federal elections for the German parliament. It combines theories of coalition politics and cabinet decision making—like prime ministerial government, collective cabinet decision making and ministerial discretion—with theoretical approaches on voting behavior to test which cabinet actor voters reward for improved economic conditions. The empirical results, which are based on data from German national election studies from 1987–2009, show that the party of the chancellor (and, thus, the strongest coalition party) benefits most from a positive evaluation of economic policy outcomes. There is, however, no consistent empirical evidence that the coalition parties collectively benefit from perceived positive economic performance. Therefore the findings demonstrate that economic voting occurs in German parliamentary elections, but is targeted specifically toward the chancellor's party.